On the estimation of the remainder term in the multidimensional integral limit theorem for the stable limit law - Banys, J. (Lithuanian Mathematical Journal, 1969)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:И. И. Банис. Об оценке остаточного члена в многомерной интегральной предельной теореме при сходимости к устойчивому законуJ Banys. Liekamojo nario įvertinimas daugiamatėje integralinėje ribinėje teoremoje stabilaus ribinio dėsnio atveju